Risk for Recurrence in Long-Term Follow-Up of Children after Liver Transplantation for Hepatoblastoma or Hepatocellular Carcinoma - Marek Stefanowicz; Piotr Kaliciński; Hor Ismail; Adam Kowalski; Dorota Broniszczak; Marek Szymczak; Katarzyna Pankowska-Woźniak; Anna Roszkiewicz; Ewa Święszkowska; Diana Kamińska; Sylwia Szymańska; Grzegorz Kowalewski (MDPI AG, 2024)
The aim of this study was to assess the long-term results of liver transplantation (LT) in pediatric patients with unresectable hepatoblastoma (HB) or hepatocellular carcinoma (HCC) with special reference to the risk of tumor recurrence. We retrospectively analyzed data from 46 HB and 26 HCC patients who underwent LT between 1990 and 2022. In HCC patients, we compared outcomes depending on donor type. We evaluated the impact of a number of risk factors on recurrence-free survival after LT. Estimated patient survival after 5, 10, and 15 years was 82%, 73%, and 73% in the HB group and 79%, 75%, and 75% in the HCC group, respectively (p = 0.76). In the HCC group, living donor LT (LDLT) and deceased donor LT (DDLT) provided similar patient survival (p = 0.09). Estimated recurrence-free survival in patients who had three or fewer risk factors was significantly better than in patients with more than three risk factors (p = 0.0001). Adequate patient selection is necessary when considering LT for primary liver tumors in children. The presence of more than three risk factors is associated with a very high risk of recurrence and indicates poor prognosis, whereas extrahepatic disease may be considered a contraindication for transplantation.